Language and Power in The Modern World - Talbot, Mary (Edinburgh University Press, 2003)
With a unique combination of selected readings and students-centered tasks in a single volume, Language and Power in The Modern World covers contemporary issues of communication theory and sociolinguistics, ranging from the global to the interpersonal. The book analyzes the key ways in which language constitutes and conveys power and social relationships in modern society, in five specific areas: multilingualism, identity, Ethnicity; Language and Youth; Language and Gender; Language and the Media; Language and Organizations.